Prevalence and outcomes of atrial fibrillation in older people living in care homes in Wales: a routine data linkage study 2003–2018. (5th December 2022) - Ritchie, Leona A; Harrison, Stephanie L; Penson, Peter E; Akbari, Ashley; Torabi, Fatemeh; Hollinghurst, Joe; Harris, Daniel; Oke, Oluwakayode B; Akpan, Asangaedem; Halcox, Julian P; Rodgers, Sarah E; Lip, Gregory Y H; et al.
Abstract: Objective: To determine atrial fibrillation (AF) prevalence and temporal trends, and examine associations between AF and risk of adverse health outcomes in older care home residents. Methods: Retrospective cohort study using anonymised linked data from the Secure Anonymised Information Linkage Databank on CARE home residents in Wales with AF (SAIL CARE-AF) between 2003 and 2018. Fine-Gray competing risk models were used to estimate the risk of health outcomes with mortality as a competing risk. Cox regression analyses were used to estimate the risk of mortality. Results: There were 86, 602 older care home residents (median age 86.0 years [interquartile range 80.8–90.6]) who entered a care home between 2003 and 2018. When the pre-care home entry data extraction was standardised, the overall prevalence of AF was 17.4% (95% confidence interval 17.1–17.8) between 2010 and 2018. There was no significant change in the age- and sex-standardised prevalence of AF from 16.8% (15.9–17.9) in 2010 to 17.0% (16.1–18.0) in 2018. Residents with AF had a significantly higher risk of cardiovascular mortality (adjusted hazard ratio [HR] 1.27 [1.17–1.37], P < 0.001), all-cause mortality (adjusted HR 1.14 [1.11–1.17], P < 0.001), ischaemic stroke (adjusted sub-distribution HR 1.55 [1.36–1.76], P < 0.001) and cardiovascular hospitalisation (adjusted sub-distribution HR 1.28 [1.22–1.34], P < 0.001). Conclusions: Older care home residents with AF have an increased risk of adverse health outcomes, even when higher mortality rates and other confounders are accounted for. This re-iterates the need for appropriate oral anticoagulant prescription and optimal management of cardiovascular co-morbidities, irrespective of frailty status and predicted life expectancy.